ADAPTING PRIMARY CARE WORKFLOWS TO PROMOTE ADVANCE CARE PLANNING WITH AN EMPHASIS ON A DEDICATED ACP FACILITATOR. (20th December 2022) - Valadares, Kevin; Leahy, Suzanne; Ehlman, Katie; Arnold, Robin
Abstract: The COVID-19 pandemic has sharpened attention regarding the need to proactively plan for a future medical crisis. Advance Care Planning (ACP) has emerged in the last 30 years as a potential way to improve individuals' end-of-life care by ensuring that patients explore and communicate personal values, goals, and preferences regarding future medical care to surrogate decision makers and medical providers. Elevating ACP as a core function of direct patient care, the University of Southern Indiana's (USI) Geriatric Workforce Enhancement Program (GWEP) embedded a multi-modal ACP initiative in a primary care clinic, anchored by the Medicare Annual Wellness Visit (AWV). Within this initiative, the role of a dedicated ACP Facilitator embedded in the practice is highlighted to promote and bill (Medicare CPT codes 99494, 99498) for ACP conversations. The addition of an ACP Facilitator (who is a licensed clinical social worker) as part of the primary care team complements the efforts of the providers to focus on What Matters most to patients. This is particularly important to patients with serious illness. This presentation will summarize the re-alignment efforts of the primary care clinic to prioritize ACP conversations for older adults, amounting to 10, 000 visits per year.